There was an old lady who swallowed a bell! - Colandro, Lucille; Lee, Jared D. (New York Scholastic, [2008], 2006)
In a twist on the classic tale of "There Was an Old Lady Who Swallowed a Fly," a ravenous old lady swallows a bell, some bows, gifts, a sack, a sleigh, and finally some reindeer.
UCWS-3243g donated by Jan Gabriel M. Castaneda - September 2013
Keywords: Children's audiobooks; Christmas--Fiction.; Stories in rhyme